Advances in Nickel-Catalyzed O-Arylation of Aliphatic Alcohols and Phenols with (Hetero)aryl Electrophiles - Morrison, Kathleen M.; Stradiotto, Mark (Synthesis, 2023)
Transition-metal catalysis has been consequential in enabling carbon–heteroatom bond-forming reactions. Recent breakthroughs in Ni-catalyzed cross-couplings have offered competitive and, in some cases, superior reactivity to Pd- or Cu-based processes. Amidst the ongoing renaissance in this field, the Ni-catalyzed C–O cross-coupling of alcohols and (hetero)aryl (pseudo)halides has surfaced as an effective strategy for the synthesis of (hetero)aryl ethers. Methodologies to achieve such transformations tend to rely on one of three catalytic approaches: (i) thermal conditions often accompanied by ancillary ligand design tailored for Ni catalysis; (ii) the synergistic combination of photoredox and Ni catalysis; or (iii) electrochemically driven Ni catalysis. In some instances, these protocols have provided access to expanded C–O cross-coupling substrate scope, including the use of inexpensive and abundant electrophile coupling partners (e.g., (hetero)aryl chlorides). This Short Review aims to summarize recent progress in the development of Ni-catalyzed O-arylations of primary, secondary, and tertiary aliphatic alcohols, as well as phenols, with (hetero)aryl electrophiles.1 Introduction2 Thermally Promoted Ni C–O Cross-Coupling2.1 Primary and Secondary Aliphatic Alcohols2.2 Tertiary Aliphatic Alcohols2.3 Phenols3 Photochemically Promoted Ni C–O Cross-Coupling3.1 Primary and Secondary Aliphatic Alcohols3.2 Phenols4 Electrochemically Promoted Ni C–O Cross-Coupling4.1 Primary and Secondary Aliphatic Alcohols5 Conclusions and Outlook
Keywords: nickel catalysis; O-arylation; synthesis; cross-coupling; etherification